Spectral singularities of differential operator with triangular matrix coefficients - Kholkin, A. M. (Methods of Functional Analysis and Topology, 2013)
For a non-selfadjoint Sturm-Liouville operator with a triangular matrix potential growing at infinity, we construct an example of such an operator having spectral singularities.